Fatigue damage and reliability assessment of subway train bogie frames under operating conditions. (January 2020) - Wang, Binjie; Sun, Shouguang; Ma, Shuang; Wang, Xi
Fatigue cracks developed on subway train bogie frames before reaching the designed lifetime, which poses great challenges to operational safety. This article presents a structural fatigue reliability assessment method combining both the in-service measurement of dynamic stress and probabilistic approach for lifetime prediction. It was found that curved interval with rail corrugation can induce the elastic vibration and the modal stress on the frame, which caused the accelerated accumulation of the fatigue damage. The predicted failure mileage for the welding joint with 99% reliability was only 340, 000 km, which agreed well with the real operation situation.